2017
DOI: 10.1038/srep40611
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Carbonylation Profile Analysis at the Critical Node of Seed Ageing in Oryza sativa

Abstract: The critical node (CN), which is the transition from the plateau phase to the rapid decreasing phase of seed ageing, is extremely important for seed conservation. Although numerous studies have investigated the oxidative stress during seed ageing, information on the changes in protein abundance at the CN is limited. In this study, we aimed to investigate the abundance and carbonylation patterns of proteins at the CN of seed ageing in rice. The results showed that the germination rate of seeds decreased by less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 57 publications
(69 reference statements)
2
32
0
2
Order By: Relevance
“…Delayed germination and subsequent slow growth are two major characteristics of aged seeds [9]. It has been reported that seed germination or seedling growth is suppressed in aged seeds, such as rice [32] and oat [33]. In this study, oat seed vigor was significantly reduced as the GP decreased from 100% to 70% after 48 d aging ( Figure 1A), together with decreased GI and VI ( Figure 1B), and depressed 10-days seedling growth ( Figure 1C-E).…”
Section: Discussionmentioning
confidence: 99%
“…Delayed germination and subsequent slow growth are two major characteristics of aged seeds [9]. It has been reported that seed germination or seedling growth is suppressed in aged seeds, such as rice [32] and oat [33]. In this study, oat seed vigor was significantly reduced as the GP decreased from 100% to 70% after 48 d aging ( Figure 1A), together with decreased GI and VI ( Figure 1B), and depressed 10-days seedling growth ( Figure 1C-E).…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies of the legume seed proteome mostly relied on gel-based techniques (typically 2D-GE and MALDI-TOF(/TOF)-MS), yielding up to several hundreds of protein identifications are available31, 32. Sample pre-fractionation [33] and isoelectrofocusing (variation of pH gradients) [31,34] do not dramatically improve the situation. In this context, due to the better resolution of RP-HPLC, an LC-MS-based approach seemed promising [14].…”
Section: Annotation Of the Pea Seed Proteomementioning
confidence: 99%
“…The germination tests do not reflect adequately the degree of seed deterioration (van de Venter 2001). Proteomic research has mainly concentrated on the negative influence of external and internal factors causing loss of seed viability (see for review Wang et al 2015), such as drying (Rajjou and Debeaujon 2008), high temperature (Zhang and Li 2015;Chen et al 2016), and high humidity and temperature (ageing) Kalemba and Pukacka 2014;Nguyen et al 2015;Li et al 2017;Yin et al 2017). Proteomic data has shown that reduction of seed longevity is often associated with oxidation of cellular macromolecules such as nucleic acids, proteins, and lipids (Sano et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al (2015) confirmed the role of antioxidant systems, and additionally illustrated the role of translation machinery and energy pathways in seed longevity. Yin et al (2017) showed that loss of seed viability is also associated with a decrease in heat shock proteins. For elm (Ulmus pumila L.), it was found that increased production of ROS during seed ageing induced alteration of specific mitochondrial proteins that may be involved in the process of mitochondrial deterioration, which led to loss of seed viability (Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%